FAKTOR-FAKTOR YANG MEPENGARUHI PENDAPATAN NELAYAN DI DESA BAJO KECAMATAN TILAMUTA KABUPATEN BOALEMO - Imbran, Harijono; Ishak, Sahrul (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to determine the factors that influence fishermen's income in Bajo Village, Tilamuta District, Boalemo Regency. This study uses a quantitative research approach. The data source was obtained through a questionnaire instrument and used 40 respondents and the analytical tool used was multiple linear regression. The results showed that there was a significant influence between the production factors X1, (Capture) X2, (Experience) X3, (Technology) and X4 (Operating Costs) on the income (Y) of fishermen in Bajo Village, Tilamuta District, Boalemo Regency. The results of multiple regression analysis produce a multiple regression equation Y = -2,446,683.31 + 0.887x1+ 0.657x2+ 0.761x3 – 0.061x4. The magnitude of the influence is indicated by the R squre value of 0.955 or 95.5 percent, meaning that both the values X1, X2, X3, and X4 greatly affect the Y value (Fishermen's Income) of 0.955 or 95.5 percent while the remaining 4.5 percent in influenced by other factors outside the research.